Vitamin K intake levels are associated with bone health in people aged over 50 years: a NHANES-based survey - Guo, Jiankui; Zhou, Ziqi; Gong, Jie; Hu, Wen; Liu, Yuan (Frontiers in Medicine, 2024)
Background: Bone health is important for older adults, and vitamin K (VK) is central to regulating bone formation and promoting bone health. However, whether VK can reduce the risk of osteoporosis and bone loss is unclear. This study hypothesized that different levels of VK intake exert varying effects on bone health in people aged over 50 years. Methods: Individuals aged above 50 years were recruited from the National Health and Nutrition Examination Survey. VK intake, based on 24-h dietary recall, was divided into three groups, namely the high, medium, and low groups, by sex and tertile. Weighted multiple logistic regression was used to investigate the effects of VK intake on the risk of osteoporosis and bone loss at the femoral neck, trochanter, intertrochanter, total femur, lumbar spine, and overall. Results: This study included 5,075 individuals. Of them, 1,001 (18%) had osteoporosis (808 women, 83%) and 2,226 (46%) had osteopenia (1,076 women, 54%). Overall, a medium level of VK intake was associated with a reduced risk of bone loss. In women, medium- [odds ratio, OR(95% confidence interval, CI): 0.66(0.47, 0.93)] and high-level [OR(95%CI): 0.71(0.52, 0.98)] VK intake were associated with a decreased risk of osteoporosis. In contrast, only medium-level VK intake was associated with a reduced risk of bone loss [OR(95%CI): 0.58(0.41, 0.81)]. Similar results were obtained for the trochanter, intertrochanter, total femur, and lumbar spine. In men, only medium-level VK intake was associated with a reduced risk of bone loss at the femoral neck [OR(95%CI): 0.66(0.48, 0.90)], whereas high-level VK intake corresponded to a reduced risk of bone loss to the lumbar spine [OR(95%CI): 0.68(0.47, 0.99)]. Nonetheless, VK intake levels did not affect the risk of osteoporosis. Conclusions: This study demonstrates sex- and bone-site-specific variations in the associations between VK intake levels and bone health in individuals aged over 50 years. Further large-scale cohort studies or randomized controlled trials are warranted to explore the effects of different VK intake levels on bone health in people regardless of their sex and bone site.